Nitrogen Dynamics and Nitrate Leaching in Intensive Vegetable Rotations in Highlands of Central Java, Indonesia - Ladiyani Retno Widowati; Stefaan De Neve (UNIVERSITY OF LAMPUNG, 2016)
High rainfall intensity is major factor governing leaching process, where leaching is often the most important process of N loss from the field and lead to agricultural environmental pollution. In order to measure the movement of mineral-N in soil profile, a field research had been conducted in two sites of center vegetable farming area with six farmer cooperators in Central Java, Indonesia. Regular soil sampling was done from Improve Practice (IP) and Farmer Practice (FP) treatment for three planting seasons during 2007. Almost all treatments FP applied higher rate of N fertilizer compare to IP, but it was not reflected in N profile. Comparison of predicted and measured mineral N content was simulated using Burns α model, then the closeness of the estimation and measured calculated using Coefficient of Residual Mass (CRM) calculation as an indicator with 0 as ideal value. Out of 9 measurements of IP and FP treatment, eight and seven measurements had negative CRM representinga slight overestimation. The NO3-N loss estimated using the Burns α model for IP and FP was in average of 67% for IP and 71% for FP of total N fertilizer added or 67% for IP and 76% for FP of total-N surplus, respectively. The calculation of potential nitrate concentration (PNC) at 1 m soil depth at the end of the third season showed a high concentration with significant different of IP and FP having mean value of 59.8 and 82.5 mg N L-1. From the gathered data it was obvious that over N fertilization had negative effect to agricultural environment.